Analisis Implementasi Sistem Pengadaan Barang dan Jasa dalam Realisasi Belanja Barang modal PT Askes (Persero) - , Ikasari ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The realizations of capital expenditure absorptions are often disapproving although the budget has been accommodated to meet the needs of each work area in the efforts to provide facilities and infrastructures. This research aims to identify the goods and services procurement system as capital expenditure realization tool of PT Askes (Limited) and perform analysis to provide recommendations in order to improve the goods and services procurement system in PT Askes (Limited). Capital expenditure budget allocation is an effort to fulfill the needs of facilities and infrastructures in supporting the conduct of operational activities. Capital expenditure budget realization is an output of goods and services procurement process which is also considered as one of the reasons of the slow/low budget realization. The research method is qualitative explanatory type in order to answer the questions of why and how a phenomenon happens. The research was done between January and June 2012. The research object is PT Askes (Limited) since based on the Law No. 24 Year 2011 about Social Security Body, in 2014 PT Askes (Limited) will be dissolved into BPJS Health. PT Askes (Limited) will prepare the infrastructures for implementing the law with significant capital expenditure budget allocation. Thus, there is a need to perform an analysis on the goods and services procurement system considering the problems that happened in the realization of capital expenditure budget in PT Askes (Limited). Based on the research done, it is found that the factors involved in the disapproving results of the capital expenditure budget realization in PT Askes (Limited) include (1) communication, lack of Goods/Services Management Guideline socialization